2016
DOI: 10.17116/jnevro201611610235-41
|View full text |Cite
|
Sign up to set email alerts
|

The three-year follow-up study of retinal changes in patients with multiple sclerosis

Abstract: RNFL and GCC thickness was significantly decreased both in MS+ON and MS-ON groups compared to controls. No difference in the annual change of RNFL thickness and GCC parameters between patients with ON and patients who did not have any visual impairment in the anamnesis was found. Changes of GCC were detected only in patients with secondary progressive MS. The study of GCC and RNFL thickness can be used to describe and characterize the level of axonal damage in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This together with the use (in some studies) of less sensitive time-domain OCT and absence of tRNFL sector analysis may partially explain the fact that previously reported longitudinal studies have not demonstrated a faster rate of axonal loss in ON eyes. 19,[32][33][34][35] In a 5-year study by Garcia-Martin et al, 32 no differences were detected between eyes with and without previous ON. Although VEP was recorded, its correlation with the rate of RNFL thinning was not analyzed.…”
Section: Discussionmentioning
confidence: 90%
“…This together with the use (in some studies) of less sensitive time-domain OCT and absence of tRNFL sector analysis may partially explain the fact that previously reported longitudinal studies have not demonstrated a faster rate of axonal loss in ON eyes. 19,[32][33][34][35] In a 5-year study by Garcia-Martin et al, 32 no differences were detected between eyes with and without previous ON. Although VEP was recorded, its correlation with the rate of RNFL thinning was not analyzed.…”
Section: Discussionmentioning
confidence: 90%